2021
DOI: 10.1038/s41598-021-88797-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of bacterial spot disease induced biotic stress in Capsicum annuum L. cultivars via antioxidant enzymes and isoforms

Abstract: Bacterial spot, caused by a group of Xanthomonads (Xanthomonas spp.), is a devastating disease. It can adversely affect the Capsicum annum productivity. Scientists are working on the role of antioxidants to meet this challenge. However, research is lacking on the role of antioxidant enzymes and their isoforms in the non-compatible pathogen and host plant interaction and resistance mechanisms in capsicum varieties. The present study was conducted to ascertain the defensive role of antioxidant enzymes and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The MDA is the dominant parameter for estimating the peroxidation of lipids 29 , 30 . Our findings revealed extreme augmentation of the MDA level, and due to the great toxicity of MDA, it could be presumed that the high prospective interaction between DNA and protein with MDA impaired these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The MDA is the dominant parameter for estimating the peroxidation of lipids 29 , 30 . Our findings revealed extreme augmentation of the MDA level, and due to the great toxicity of MDA, it could be presumed that the high prospective interaction between DNA and protein with MDA impaired these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The current study therefore showed that increasing polyphenol oxidase activity can boost the resistance of sweet pepper plants to Xanthomonas vesicatoria -induced bacterial leaf spot disease. Several studies have shown that after pathogen infection, POX, CAT, PPO, and SOD enzyme activity increased in resistant cultivars compared to susceptible cultivars, implying that antioxidant enzymes and isoforms can mitigate bacterial spot disease-induced biotic stress in Capsicum annuum L. cultivars [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium attacks leave, fruits, and stems causing blemishes on these plant parts. It is a gram-negative, rod-shaped bacterium that can survive in seeds and plant debris from one season to another 3 – 5 . The pathogen can devastate a pepper crop by early defoliation of infected leaves and disfiguring fruit.…”
Section: Introductionmentioning
confidence: 99%